Editing Strategies for Overcoming Instrumentation Issues in Rebay’s Großes Duo in a-Moll - Mantovani, Luiz (Revista Vórtex, 2020)
This article looks at contextual and interpretive issues surrounding the Großes Duo in a-Moll by Viennese composer Ferdinand Rebay (1880-1953). After situating Rebay within the contemporary guitar developments in Vienna, I contextualize the piece and highlight its significance as a one-of-a-kind Romantic sonata for guitar duo. Next, I look at the potential difficulties of incorporating it into the repertoire of modern guitar duos due to Rebay’s use of a near-obsolete instrument, the Quintbass Gitarre, while also offering a brief organological investigation. Finally, I describe in detail my attempts to adapt the piece to the instrumentation of my ensemble, the NOVA Guitar Duo. Backed up by an extensive familiarity with the composer’s style, I endeavour to intervene in the text, not only for playability reasons but also to rebalance melodic material in the fashion of traditional guitar duo and domestic Austro-German chamber music writing.